OPTIMALISASI DALAM PENGELOLAAN RUANG TERBUKA HIJAU PUBLIK TAMAN KOTA DI KOTA BANJARBARU - Forasidah Forasidah (Jurnal PubBis, 2021)
This study aims to: (1) Know the form of the government's response to the optimization of Green Open Space Management in the City of Banjarbaru. (2) Knowing the Public Understanding of Green Open Space Management in Banjarbaru City. And (3) Knowing what are the guardians of improving the optimization of Green Open Space Management in the City of Banjarbaru. This research refers to the management indicators of J George R Terry's theory, while the method used in this research is a mixed method using a sequential type of explanation design, where in this study collect and analyze qualitative data then collect and analyze quantitative data. The results of research on optimization in the management of public green open spaces in city parks in Banjarbaru City have been running "well". This can be explained from the findings (1) In terms of planning, the Municipal Government of Banjarbaru carries out green planning and design which is packaged into a planning model of "Smart Green City for Banjarbaru". (2) In terms of utilization, it is prioritized for recreational activities, sports, and a place to study for students in nature as well as utilization as groundwater absorption to overcome flood disasters. (3) In the event that the Banjarbaru City Government guidance is carried out in the form of socialization regarding what is the use of a public Green Open Space for the community and under the supervision of the Banjarbaru City Government, an appeal and installation of notification boards so that it is not harmed, throwing garbage in the Public Green Open Space area and prohibiting the construction of houses or seizure of land without permission. Meanwhile, the obstacles found in increasing the optimization of Green Open Space Management in Banjarbaru City are: (1) there is a debate between landowners to acquire their land to become utility land or Public Green Open Space. (2) lack of public awareness regarding the use of public green open space. (3) lack of Human Resources in terms of overseeing the Green Open Space area and also the role of the Banjarbaru City Civil Service Police Unit which is lacking in overseeing the Public Green Open Space area.